MicroRNA-223 and microRNA-92a in stool and plasma samples act as complementary biomarkers to increase colorectal cancer detection - Chang, Pi-Yueh (Oncotarget, 2016)
Aberrant levels of circulating miRNAs are potential biomarkers for the early detection of colorectal cancer (CRC). However, no previous systematic study has examined miRNAs in various specimen types from the same patient to evaluate their clinical utility. In this study, we compiled information from ∼450 articles published before 2012, and selected the 46 most frequently reported CRC-related miRNAs as candidates. We then established a 46-miRNA multiplex RT-qPCR method, and efficiently examined two clinically accessible samples: stool from fecal occult blood test and EDTA plasma. A total of 62 tissue, 447 stool, and 398 plasma samples were collected from CRC patients and healthy controls. Good correlations of detectable miRNAs were noticed in paired tumor tissues, stool, and plasma samples of 62 CRC patients. Using these 62 CRC patients and 62 matched healthy controls as the training set, 5 and 11 differentially expressed miRNAs achieved the area under the ROC curve (AUC) greater than 0.7 in stool and plasma samples, respectively. The selected miRNAs was subsequently validated using the remaining enrolled samples as the test cohort; 4 miRNAs in stool and 6 miRNAs in plasma were maintained discriminating powers for CRC patients. After examining the complementary effect, combined analysis of miR-223 and miR-92a, which were commonly present in stool and plasma samples, yielded the highest sensitivity of 96.8% and the specificity of 75% for CRC (AUC = 0.907). These results allowed us to establish a two-miRNA biosignature in two types of CRC clinical specimens with a high sensitivity for CRC detection.